Elimination and prevention of iodine deficiency in pregnant women from Peru - Pretell Zárate, Eduardo (2022)
Iodine is an essential element for synthesizing thyroid hormones, it is also essential for cell metabolism and tissue development, especially in the brain. Iodine requirements are higher during pregnancy and lactation. Iodine deficiency (ID) is a widespread condition all over the world; it is frequent in Peruvian highlands and rainforest. ID causes damage in all life periods, and vulnerability for this is greater during pregnancy and infancy. Universal salt iodination (USI) for human use is the most cost-effective and sustainable strategy for controlling ID. Peru has achieved the sustained elimination of iodine deficiency disorders (IDD) since 1994. Objective. To determine the effectiveness of the national program for controlling IDDs and the USI strategy for complying with the increased iodine requirement and to assure optimal iodine nutrition in pregnant women from the Peruvian highlands, a region with severe natural iodine deficiency. Material and Methods. The study included 489 pregnant women from the highlands, who were selected from those attending prenatal assessment in healthcare centers. Iodinated salty consumption was verified in each subject and a casual urine sample was collected for measuring iodine and creatinine concentration. Results. According to the admission survey, 99.6% of household use iodinated salt. The overall mean of iodine urine concentration (IUC) was 209 μg/L, which is well within the adequate range for pregnant women, and it shows a normal iodine nutrition status. The creatinine urinary concentration was normal. Conclusion. These results confirmthe efficiency and success of the national program for the sustained elimination of IDDs, assuring normal iodine nutritional supply during pregnancy; and, therefore, preventing the risk for brain damage in newborns every year in the highlands.